Altered expressions of circulating microRNAs 122 and 192 during antitubercular drug induced liver injury indicating their role as potential biomarkers. (September 2021) - Bakshi, S; Kaur, M; Saini, N; Mir, AA; Duseja, A; Sinha, SK; Sharma, S
Drug induced liver toxicity is a serious health complication leading to high mortality rates and post marketing withdrawal of drugs. Although considered to be the gold standard biomarkers; aspartate aminotransferase, alanine aminotransferase, total bilirubin and alkaline phosphatase have been found to have specificities beyond liver, therefore more specific and predictive markers for the detection of antitubercular drug mediated liver damage are required. Unfortunately, the effectiveness of currently used first line antitubercular drugs namely isoniazid, rifampicin, pyrazinamide is often accompanied with liver injury, impeding the cure of patients. Keeping in view, the prognostic and diagnostic applications of microRNAs in various diseases, we tried to assess the importance of microRNAs 122 and 192 in antitubercular drug associated liver injuries. The study included subjects having tuberculosis of any type with antitubercular drug induced liver injury; naïve or newly diagnosed tuberculosis patients, tuberculosis patients on drugs not having toxicity and healthy controls. Observations from this study revealed that expression levels of miR-122 and miR-192 were significantly decreased in the serum of antitubercular drug induced liver injury patients only. Therefore, these microRNAs or the pathways associated with them can be used as a tool to predict or cure antitubercular drug associated liver injury in future.